Analysis of the interactions between climate data and the desertification process in the desertification hotspot of Cabrobó-PE, Brazil - Vieira, Rita Marcia da Silva Pinto; Cunha, Ana Paula Martins do Amaral; Barbosa, Alexandre Augusto; Ribeiro Neto, Germano Gondim; Tomasella, Javier; Alvalá, Regina Célia dos Santos; Santos, Fabrícia Cristina; Santana, Marcos de Oliveira (Sustainability in Debate, 2018)
This study assessed the dynamics of the Land Use and Land Cover Changes in the desertification hotspot of Cabrobó-PE using an approach that includes the space-time variation of environmental and climate data. To achieve this goal, the ArcGis software and the Google Earth Engine Platform were used. This platform combines a catalog of satellite imagery and geospatial datasets with planetary-scale analysis capabilities and makes it available for scientists, researchers, and developers allowing the detection of changes, map trends, and quantify differences on the Earth's surface. Results showed that forested areas decreased 54% between 2000 and 2016, being replaced by areas of bare soil and degraded areas. The degraded areas were characterized by higher land surface temperature (37.5% °C) and by an increase of 1°C in the period 2009 to 2016. The increase in land surface temperature may be associated with the water stress, which usually worsens in areas with a high degree of soil degradation. The combination of the information analyzed in the present study allows the monitoring of heterogeneous areas, identifying hotspots that require immediate recovery actions and the improved of soil management.